"Self‐Lockable" Liquid Crystalline Diels–Alder Dynamic Network Actuators with Room Temperature Programmability and Solution Reprocessability. (18th February 2020) - Jiang, Zhi‐Chao; Xiao, Yao‐Yu; Yin, Lu; Han, Li; Zhao, Yue
Abstract: Novel main‐chain liquid crystalline Diels—Alder dynamic networks (LCDANs) were prepared that exhibit unprecedented ease for actuator programming and reprocessing compared to existing liquid crystalline network (LCN) systems. Following cooling from 125 °C, LCDANs are deformed with aligned mesogens self‐locked at room temperature by slowly formed Diels–Alder (DA) bonds, which allows for the formation of solid 3D actuators capable of reversible shape change, and strip walker and wheel‐capable light‐driven locomotion upon either thermally or optically induced order–disorder phase transition. Any actuator can readily be erased at 125 °C and reprogrammed into a new one under ambient conditions. Moreover, LCDANs can be processed directly from melt (for example, fiber drawing) and from solution (for example, casting tubular actuators), which cannot be achieved with LCNs using exchangeable covalent bonds. The combined attributes of LCDANs offer significant progress toward developing easily programmable/processable LCN actuators. Abstract : Flüssigkristalline dynamische Netzwerke können bei Raumtemperatur zu 3D‐Objekten geformt werden, während sie durch langsam gebildete Diels‐Alder(DA)‐Vernetzungen stabilisiert werden. Die Aktoren zeigen thermisch oder optisch induzierte reversible Formänderungen zum Verrichten von mechanischer Arbeit oder zur Fortbewegung.